Assessing the effectiveness of fire prevention strategies. Issue 6 (18th August 2019) - Taylor, Mark; Appleton, Deb; Keen, Guy; Fielding, John
ABSTRACT: The authors examined the process of assessing the effectiveness of fire prevention within a Fire and Rescue Service in north west England, demonstrating how this was applied in practice. The approach to fire prevention strategy assessment included overall fire and rescue service performance, performance in relation to different population segments, cost per head performance, and multi-agency collaboration to support an effectiveness-based rather than outcomes-based performance assessment. IMPACT: This case study examination of the effectiveness of fire prevention strategies shows that fire prevention activities have a clear impact on the reduction of the number of fires. Major lessons for other fire and rescue services include that referrals to partner agencies were appropriate to assist in reducing factors associated with fire risk. In addition, concentrating fire prevention on the elderly was important given the proportion of fire fatalities and injuries involving this group. Finally, analysis of the effectiveness of fire prevention activities can inform fire prevention strategies.